Optical coherence tomography for characterization of nanocomposite materials - Schneider, Simon (Karlsruhe Series in Photonics & Communications, 2021)
Major challenges in nanoparticle and nanocomposite development are the control of particle size and shape, and to achieve uniform particle dispersion. In this book, the application of optical coherence tomography (OCT) for nanocomposite and nanoparticle characterization is investigated. Industrial requirements are robustness, small system cost and size, and an open path towards parallelization. We design and investigate silicon photonic integrated OCT systems that comply with these requirements.